2021
DOI: 10.1007/s00221-020-06030-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of delta and theta oscillations during ego-motion in healthy adult volunteers

Abstract: The successful cortical processing of multisensory input typically requires the integration of data represented in different reference systems to perform many fundamental tasks, such as bipedal locomotion. Animal studies have provided insights into the integration processes performed by the neocortex and have identified region specific tuning curves for different reference frames during ego-motion. Yet, there remains almost no data on this topic in humans.In this study, an experiment originally performed in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 64 publications
(82 reference statements)
1
10
0
Order By: Relevance
“…By contrast, event-related synchronizations/desynchronizations are time-locked events, but not phase-locked events, reflecting more neuronal and synaptic characteristics, network connectivity, and modulation on more or less extended neuronal assemblies ( 220 ). A few studies investigated both VestEPs and responses in the time-frequency domain ( 32 , 111 , 166 , 167 , 171 ). Rotations were found to induce alpha rhythm desynchronization in central and parietal scalp regions ( 32 , 171 ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…By contrast, event-related synchronizations/desynchronizations are time-locked events, but not phase-locked events, reflecting more neuronal and synaptic characteristics, network connectivity, and modulation on more or less extended neuronal assemblies ( 220 ). A few studies investigated both VestEPs and responses in the time-frequency domain ( 32 , 111 , 166 , 167 , 171 ). Rotations were found to induce alpha rhythm desynchronization in central and parietal scalp regions ( 32 , 171 ).…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies using body translations revealed a positive component with a peak latency of 199 ms, best observed under electrode Cz [( 33 , 166 , 167 ); Figure 5B ]. As for the n80, the p199 amplitude increased with body acceleration and this increase was best explained by increased activity in the cingulate sulcus visual area.…”
Section: Late Latency Vestibular-evoked Potentialsmentioning
confidence: 92%
See 3 more Smart Citations